2020
DOI: 10.1002/dta.2901
|View full text |Cite
|
Sign up to set email alerts
|

New psychoactive substances on dark web markets: From deal solicitation to forensic analysis of purchased substances

Abstract: The dark web scene has been drawing the attention of law enforcement agencies and researchers alike. To date, most of the published works on the dark web are based on data gained by passive observation. To gain a more contextualized perspective, a study was conducted in which three vendors were selected on the "Dream Market" dark web marketplace, from whom subsequently several new psychoactive substances (NPS) were ordered. All transactions were documented from the initial drug deal solicitation to the final q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In recent years, specialized websites have appeared on the darknet as an alternative way to obtain illegal products. Even though several markets have closed since 2018, the darknet still plays a key role in the worldwide diffusion of NPS (6,12,13). Although the drugs found on the darknet represent 0.2% of the retail sales in western countries, a sharp increase of the darknet drug trade was reported in Europe during the first 3 months of 2020 (10,11).…”
Section: Impact Of International Restrictions On Drug Production Tramentioning
confidence: 99%
“…In recent years, specialized websites have appeared on the darknet as an alternative way to obtain illegal products. Even though several markets have closed since 2018, the darknet still plays a key role in the worldwide diffusion of NPS (6,12,13). Although the drugs found on the darknet represent 0.2% of the retail sales in western countries, a sharp increase of the darknet drug trade was reported in Europe during the first 3 months of 2020 (10,11).…”
Section: Impact Of International Restrictions On Drug Production Tramentioning
confidence: 99%
“…It could therefore be concluded that the criminal element itself has been taking advantage of remote interactions and transactions as the pandemic set in, exhibiting a considerable level of adaptability [ 19 ]. The rise in the consumption of novel psychoactive substances, extremely elusive and hard-to-detect substances intended to replicate the effects of illegal drugs of abuse [ 20 , 21 , 22 , 23 ] is worrisome and may pave the way for trafficking and addiction dynamics much harder to supervise and address over time with all the mental health implications such a shift could produce [ 24 , 25 ]. Telemedicine/telepsychiatry may be an extra arrow in our quiver to stem the tide of SUD pervasiveness as a major mental and public health threat and to reach many individuals in a state of vulnerability who would not otherwise seek care at health facilities.…”
Section: Methodsmentioning
confidence: 99%
“…Only two studies have been published where the research teams purchased psychoactive substances directly from cryptomarket listings for the purposes of chemical analysis (Rhumorbarbe et al , 2016; Jurásek et al , 2021). Rhumorbarbe et al (2016) received legal authority to purchase drugs from Swiss-based cryptomarket vendors.…”
Section: Introductionmentioning
confidence: 99%
“…Rhumorbarbe et al (2016) found the products purchased from the same listing were of similar purity. Jurásek et al (2021) purchased nine samples of new psychoactive substances (NPS; that at the time of purchase were not yet illegal) from six vendors on one market. The research team analysed the contents of the samples and found that only one sample contained the advertised substance.…”
Section: Introductionmentioning
confidence: 99%